Biomarkers and surrogate endpoints in randomized clinical trials - Buyse, Marc (Henry Stewart Talks, 2007)
Definitions (prognostic biomarker, predictive biomarker, surrogate endpoint), Statistical validation of biomarkers, Examples of surrogate endpoints in oncology
Updated at 2016/09/29